2013
DOI: 10.4103/2278-0203.115090
|View full text |Cite
|
Sign up to set email alerts
|

Sex determination potential of permanent maxillary molar widths and cusp diameters in a North Indian population

Abstract: Aims:To assess the sex discrimination potential of permanent maxillary molar crown widths and cusp diameters.Materials and Methods:Measurements were made on plaster casts of 200 individuals of known sex (100 males, 100 females, aged 12-21 years). Eight parameters were measured on the first and second maxillary molars with a digital caliper [buccolingual, mesiodistal, mesiobuccal-distolingual and distobuccal-mesiolingual crown widths and cusp diameters (hypocone, protocone, paracone, and metacone)]. The percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 12 publications
(15 reference statements)
4
11
2
Order By: Relevance
“…The observation on the relative dimensions of the buccolingual and mesiodistal widths was in tandem with previous studies [91213141920]. It was also consistent with Sharma et al [11] in the case of maxillary SM; but on the contrary, it was at variance with the latter in the case of maxillary FM. The reason for this may be because the MD is limited by teeth at both the mesial and distal contact points in contrast to the BL that does not have dental structures limiting it.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The observation on the relative dimensions of the buccolingual and mesiodistal widths was in tandem with previous studies [91213141920]. It was also consistent with Sharma et al [11] in the case of maxillary SM; but on the contrary, it was at variance with the latter in the case of maxillary FM. The reason for this may be because the MD is limited by teeth at both the mesial and distal contact points in contrast to the BL that does not have dental structures limiting it.…”
Section: Discussionsupporting
confidence: 91%
“…Some studies have been conducted among different peoples of the world with a focus on dimorphic status of permanent maxillary molar crown or cusp, or combination of both [8910111213141516].…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] The importance of odontometrics in gender determination is reflected in various studies carried out on the subject across the globe. [ 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 ] The present study endeavors to evaluate morphometric measurements of the permanent maxillary dentition including central incisor, canine, first premolar and the first molar (representative teeth of each series) for sexual dimorphism and to estimate the level of accuracy with which they could be used for gender determination.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, cuspal dimensions aid in diagonal measurements due to its different evolutionary background and growth pattern. [8] According to Hillson, most of the times teeth were attrited limiting the usefulness of tooth crown diameter measurements as they are usually defined at the widest points of the crown. [3] Univariate analysis of previous studies showed that the mesiodistal dimensions of male teeth were greater than female dentitions for all individual type of tooth in both maxillary and mandibular arches (Richardson et al).…”
Section: Discussionmentioning
confidence: 99%